Critical Success Factors – a study of Project Management techniques using Pinto’s Model in the Malaysia housing construction companies perspective - Eng, Swee Huat (2014)
Non-familiarity and not being well versed with project management knowledge areas and processes, the use of project management tools and techniques, standardizations, consistency and optimization of the project management processes implementation which lead to unnecessary schedule delays, cost overruns, poor quality, overlooked risks and scope creep are among the host of issues associated with Project Management over the project life cycle. Each housing construction company strives to achieve the most efficient and effective project management processes to achieve project success and each manages project management processes differently. This study investigates the importance placed by the respective stakeholders of the construction companies in managing project management processes in housing constructions projects based on the nine project management knowledge areas and ten elements of the “project implementation profile”. Data was collected through the questionnaires where the questionnaire used the Likert Scale to evaluate the data. Due to insufficient data, interviews with relevant personnel were conducted. Based on the questionnaires and interviews, there seem to be initiatives taken by the Company in attaining project success in constructions projects. The study finds that the stakeholders and Companies are practicing Project management processes in their construction projects. It is proposed that construction companies implement, standardize, institutionalize and optimize project management processes and usage in order to avoid financial losses, cost overruns, legal disputes and other problems to increase the probability of project success. (Abstract by author)